Fosforilannoituksen porraskokeet 1977-1994 : vuosittain annetun fosforimäärän vaikutus maan viljavuuteen ja peltokasvien satoon monivuotisissa kenttäkokeissa - Saarela, Into; Järvi, Aulis; Hakkola, Heikki; Rinne, Kalle (Maatalouden tutkimuskeskus, 1995)
Phosphorus fertilizer rate trials, 1977-1994. Effects of the rate of annual phosphorus application on soil fertility and yields of field crops in long-term field experiments
Keywords: Ka; fosforilannoitus; fosforin otto; fosforitase; jälkivaikutus; kasvianalyysi; kasvin fosfori; lannoituskustannus; maa-analyysi; maan fosfori; maan viljavuus; fosfori; peltoviljely; fertilizer costs; field crops; optimum fertilization; phosphorus balance; phosphorus fertilization; phosphorus uptake; plant analysis; plant phosphorus; residual effect; soil fertility